2010
DOI: 10.1080/18811248.2010.9711947
|View full text |Cite
|
Sign up to set email alerts
|

Countercurrent Extraction Test with Continuous Flow of Molten LiCl-KCl Salt and Liquid Cd for Pyro-Reprocessing of Metal FBR Fuel

Abstract: The three-stage countercurrent extraction test with molten LiCl-KCl and liquid Cd was carried out for the development of spent salt treatment process in pyrometallurgical reprocessing of metal FBR fuel. Both salt and Cd solvent were supplied successively from each feed tank into the extractor at a constant flow rate and recovered separately into individual recovery tanks. Uranium, transuranic elements, and rareearth elements were substituted by Ce, Gd, and Y, respectively. More than 98% of Ce and 93% of Gd wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…This is in line with the results of Kurata et al [4]. Equilibration studies reported by Kurata et al [4] revealed that distribution coefficient of actinides between salt and cadmium alloy is dependent on lithium concentration in the cadmium phase. For 10% excess of lithium above the required stochiometric concentration in cadmium phase, the equilibrium distribution coefficient is two orders of magnitude or higher.…”
Section: × 100%supporting
confidence: 90%
See 1 more Smart Citation
“…This is in line with the results of Kurata et al [4]. Equilibration studies reported by Kurata et al [4] revealed that distribution coefficient of actinides between salt and cadmium alloy is dependent on lithium concentration in the cadmium phase. For 10% excess of lithium above the required stochiometric concentration in cadmium phase, the equilibrium distribution coefficient is two orders of magnitude or higher.…”
Section: × 100%supporting
confidence: 90%
“…This is done by reductive liquid-liquid extraction using cadmium-lithium alloy. Earlier Kinoshita et al [3,4] have reported studies on the reductive extraction of Ce, Gd and Y from the salt using single stage and three stage continuous extractors by considering the Ce and Gd are surrogates for the actinides. As part of the development efforts on pyrochemical reprocessing, an experimental facility has been installed inside an argon atmosphere glove box for carrying out studies on the actinide draw down process.…”
Section: Introductionmentioning
confidence: 99%
“…An electrorefiner equipped with a concentrically configured anode/solid cathode module and a mechanism for scraping off cathode deposits was developed to increase the uranium recovery rate. Figure 11 shows the anode/solid cathode module installed in Ar atmosphere glove box (18). Stalling of the anode and scraper rotation due to the interference by the cathode deposits was completely diminished by the modifications in the design of the anode basket and scraper mechanism.…”
Section: Electrorefiner Developmentmentioning
confidence: 99%